Public Expenditure and Economic Growth in Nigeria: Health and Education Nexus - Emmanuel Disi (INTERNATIONAL JOURNAL OF ECONOMICS AND FINANCIAL MANAGEMENT, 2026)
The study investigated the effect of public expenditure and economic growth in Nigeria spanning from 2001 to 2024, using annual time series data sourced from Central Bank of Nigeria (CBN) statistical bulletin, World Bank Indicator (WDI), and National Bureau of Statistic (NBS). Variables utilized in the study are real gross domestic product, public expenditure on health, public expenditure on education, public expenditure administration, literacy rate and life expectancy. Autoregressive Distributed Lag (ARDL) procedure was used as estimation technique. The findings revealed that in the short run, expenditure on health proved negative and statistically significant; the lag value had positive and statistically significant in the current year period, but in the long run, expenditure on health revealed negative and statistically significant effect; education revealed positive but statistically insignificant in the short run, the lag value proved negative and statistical significant in the current period, but in the long run, education revealed robust and positive; administration maintained positive and statistical significance in both terms. Literacy rate proved negative and statistically significant in both terms; life expectancy proved positive but statistically insignificant, but negative and statistically insignificant in the long run. The study concluded that true prioritization, adequate funding and timely monitoring across sectors are needful. And therefore, recommended amongst others, the introduction of a block-chain financing platform as a central payment system, workforce development, facility upgrades, and encouragement of collaboration between academia and industries to commercialize research outputs.